This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let x = 6 + 6 + 6 + …
Since n = n 2 1
n 2 = n
x 2 = 6 + 6 + 6 + … 2 = 6 + 6 + 6 + 6 + …
If we then take x from x 2 we get
x 2 − x = 6
This can be re-written as a quadratic equation
x 2 − x − 6 = 0
Putting this into the quadratic formula we get
x = 2 1 ± ( − 1 ) 2 − 4 ( 1 ) ( − 6 )
This simplifies down to
x = 2 1 ± 2 5
Which then means that
x = 2 1 ± 5
This gives a positive and negative value of x
x = 3 and x = − 2
Since the question asked for a positive value the answer is 3
Consider given =y then given can be written as (6+y)^(1/2)=y
Squaring both sides we have y^2-y-6=0 i.e
(y+2)(y-3)=0 i.e y=-2 and y=+3 rejecting -ve value we have y=given=3
Problem Loading...
Note Loading...
Set Loading...
L e t x = 6 + 6 + 6 + . . . x 2 = 6 + 6 + 6 + 6 + . . . S i n c e x = 6 + 6 + 6 + . . . x 2 = 6 + x x 2 − x − 6 = 0 ( x − 3 ) ( x + 2 ) = 0 x = 3 ( x > 0 ) T h e r e f o r e , 6 + 6 + 6 + . . . = 3